Reduced symptom burden with the support of an interactive app during neoadjuvant chemotherapy for breast cancer – A randomized controlled trial. (June 2020) - Fjell, Maria; Langius-Eklöf, Ann; Nilsson, Marie; Wengström, Yvonne; Sundberg, Kay
Abstract: Objectives: Neoadjuvant chemotherapy causes distressing symptoms, which have to be managed by patients at home. Assessing and acting upon relevant patient-reported symptoms regularly with the support of mHealth such as apps, has shown to decrease symptom burden and improve health-related quality of life (HRQoL). There is a lack of apps for patients with breast cancer which are tested in rigorous trials and only a few include interactive components for immediate clinical management. The aim of this study was to evaluate whether the use of the interactive app Interaktor improves patients' levels of symptom burden and HRQoL during neoadjuvant chemotherapy for breast cancer. Materials and methods: This randomized controlled trial included patients in an intervention group (n = 74) and a control group (n = 75), recruited at two university hospitals in Stockholm, Sweden. The intervention group used Interaktor for symptom reporting, self-care advice and support from health-care professionals during treatment, and the control group received standard care alone. Self-reported symptoms and HRQoL were assessed at two time points to determine differences between the groups. Results: The intervention group rated statistically significant less symptom prevalence in nausea, vomiting, feeling sad, appetite loss and constipation. Overall symptom distress and physical symptom distress were rated statistically significant lower in the intervention group. Further, emotional functioning was rated statistically significant higher in the intervention group. Conclusions: By using the Interaktor app in clinical practice, patients get individual support when managing treatment-related symptoms during neoadjuvant chemotherapy for breast cancer, leading to decreased symptom burden and improved emotional functioning. Highlights: Using the app Interaktor reduced symptom burden in patients with breast cancer. The use of Interaktor enhanced emotional functioning during treatment. Interaktor provided individual support during neoadjuvant chemotherapy. Use of Interaktor allowed breast cancer patients for daily reflection over symptoms.